The Concept of Man in F. Scott Fitzgerald's Novels - Miller, Lawrence E. (My University, 1967)
In F. Scott Fitzgerald's four finished novels and the fragment of the fifth, he gradually worked out a distinctive concept of man. He found three basic types: The Nietzschian, firmly the convinced of the rectitude of a project; the "stupid" (without the usual perjorative connotations), who never consider the possibility or desirability of a set goal; and the Tolstoian, searching for some satisfactory way to be, discovering possible ways by watching other people. The Tolstoians adopt provisional ways to be --"poses" --, changing whenever they recognize a better. Fitzgerald develops three basic problems facing the Tolstoians, investigates the possibilities for love, and discovers some implications of time and death.
Keywords: English; English Language and Literature; English Language and Literature